2003
DOI: 10.1124/jpet.103.059899
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Nicotine Exposure Attenuates Nicotine-Stimulated Dopamine Release in the Nucleus Accumbens Shell of Adolescent Lewis Rats

Abstract: The effects of chronic gestational exposure to nicotine on the nucleus accumbens dopamine response to acute nicotine were determined during adolescence (postnatal day 29 -36) in crossfostered and noncross-fostered Lewis rats. In both males and females, gestational nicotine exposure diminished the adolescent nucleus accumbens dopamine response to 0.07 mg/kg nicotine i.v. (p Ͻ 0.05). However, dopamine responses to 0.105 mg/kg nicotine were unaffected by gestational nicotine treatment and were similar in both gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 29 publications
1
63
0
Order By: Relevance
“…However, Shacka et al (1997) found that the same nicotine challenge dose only increased activity in 14-day old male rats prenatally exposed to nicotine. These findings are interesting in light of studies showing reduced activity of cholinergic and catecholaminergic systems in rats prenatally exposed to nicotine, an effect one might expect to influence nicotineinduced locomotor activity (Kane et al 2004;Slikker et al 2005;Slotkin 1998). The discrepancy between studies may be due to differences in the postnatal time point at which nicotine-induced locomotor behavior was measured, since neuropharmacological sequelae of prenatal nicotine exposure are known to vary over the course of postnatal development.…”
Section: Discussionmentioning
confidence: 90%
“…However, Shacka et al (1997) found that the same nicotine challenge dose only increased activity in 14-day old male rats prenatally exposed to nicotine. These findings are interesting in light of studies showing reduced activity of cholinergic and catecholaminergic systems in rats prenatally exposed to nicotine, an effect one might expect to influence nicotineinduced locomotor activity (Kane et al 2004;Slikker et al 2005;Slotkin 1998). The discrepancy between studies may be due to differences in the postnatal time point at which nicotine-induced locomotor behavior was measured, since neuropharmacological sequelae of prenatal nicotine exposure are known to vary over the course of postnatal development.…”
Section: Discussionmentioning
confidence: 90%
“…Nicotinic receptors are abundant on dopamine terminals, particularly in the striatal regions, leading to the vulnerability of these cells to the toxic effects of nicotine [15]. Research has shown that prenatal administration of nicotine decreases the sensitivity of dopaminergic cells in the nucleus accumbens to administration of acute doses of nicotine later in life, indicating that these cells required higher levels of stimulation to instigate dopamine release [43]. Furthermore, both cell numbers and transcription rates of nicotinic receptors in dopaminergic cells of the ventral tegmental area (VTA) are reduced following prenatal nicotine administration, affecting dopaminergic action in both the VTA and its target regions including the nucleus accumbens and prefrontal cortex through adolescence [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study using double our prenatal concentration of dexamethasone in the drinking water made a detailed analysis of maternal behavior in the first week after birth and reported a positive rather than negative effect (Hauser et al, 2006). It would also appear that cross-fostering per se may not be without significant effects on maternal behaviors (Maccari et al, 1995) and has been reported to reduce baseline and nicotine-stimulated DA secretion in the nucleus accumbens (Kane et al, 2004). On the other hand, certain programming effects of prenatal dexamethasone treatment were unaffected by cross-fostering to control dams, suggesting that the GC effects operate directly in the fetus (Nyirenda et al, 2001).…”
Section: Dexamethasone Treatment Regimensmentioning
confidence: 99%